Methodological stakes around the "heritage - tourism - development" triangulation in the Democratic Republic of the Congo - Yves Robert (Via@)
The question of the representation of the Democratic Republic of the Congo on the UNESCO lists of tangible world heritage (1972 Convention) and intangible world heritage (2003 Convention) is currently being raised in the Congo (DRC) by various Congolese and Belgian partners on the occasion of a common collaboration program. At the root of their reflections is the observation of the under-representativeness of the Congolese cultural heritage in these UNESCO documents. It was straightaway agreed upon to refuse to approach the notion of heritage from a solely backward-looking angle. Among the ideas which stir the ongoing debates, the stake of the relations between the concepts of heritage, development and tourism is identified as a priority approach for this country, which is in the process of economic reconstruction and in the stage of peace consolidation. The question of a territorialized heritage closely related to social and economic dynamics and environmental problems (such as cultural landscapes, ancient urban centers, cultural routes), gave rise to a body of thought questioning the notion of “neighborhood tourism” genuinely profitable to local populations (unlike what is known as “community tourism”), without refusing the more usual approaches which promote international tourism.